Historical Positivism and Axiological Criticism: A Critique of Qur'anic Reasoning on 20th-Century Indonesian Islamic Historiography - Moeflich Hasbullah; Asep Saeful Mimbar (Jurnal Iman dan Spiritualitas, 2026)
The writing of Islamic history (historiography) in Indonesia throughout the 20th century has experienced very rapid methodological progress, but on the other hand, faces serious challenges related to the drought of axiological values. This article aims to conduct a critical analysis of the development of 20th-century Indonesian Islamic historiography using Qur'anic reasoning as an analytical tool. The method used is qualitative with an intellectual history approach and discourse analysis. The results of the study show that the transition from traditional historiography to the academic-scientific tradition, pioneered by figures such as Hoesein Djajadiningrat and Azyumardi Azra, has succeeded in placing the history of Islam in the archipelago in a competitive global scientific standard. However, the dominance of the positivist paradigm in these Muslim works tends to reduce religious phenomena to mere empirical variables separated from transcendental values. Axiological criticism based on Qur'anic reasoning offers a new orientation that views history not only as an objective reconstruction of the past, but also as an instrument of social transformation and a moral message ('ibrah) for the future (li-ghad). This article concludes with the need to synthesize the sophistication of modern methodology with the Islamic worldview to produce a historiography that is not only scientifically accurate but also spiritually meaningful and emancipatory for human civilization.